The Clinical Importance of the Mercury Problem in Artisanal Small-Scale Gold Mining - Justice Afrifa; Justice Afrifa; Yeboah Kwaku Opoku; Yeboah Kwaku Opoku; Eric Ofori Gyamerah; George Ashiagbor; Rosemary Doe Sorkpor (Frontiers Media S.A., 2019)
Artisanal small-scale mining is widely operated in various countries serving as a livelihood to many rural communities. However, it is a significant source of environmental mercury contamination which affects human health. Amalgamation and amalgam smelting, two significant steps in the artisanal small-scale mining operations generate lots of mercury vapors, leading to chronic exposure among miners. Thus, this article seeks to provide a topical review of recent findings on organ damage and metabolic disorders among mercury-exposed artisanal small-scale miners with emphasis on the contributing factors such as personal protective equipment usage and artisanal small-scale gold mining-specific occupational activities. Also, insights into the effect of mercury intoxication and mechanisms of action on organ and metabolic systems among exposed individuals are provided.